2002
DOI: 10.1046/j.1525-1470.2002.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

A 13‐Year‐Old Girl with Recessive Dystrophic Epidermolysis Bullosa Presenting with Squamous Cell Carcinoma

Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) is an uncommon and severely disabling genetic disorder characterized by trauma-induced blisters, intractable skin ulcers, scarring, milia, and nail dystrophy. Patients with RDEB have an increased tendency for fast-growing and early metastasizing squamous cell carcinoma (SCC). We report here a 13-year-old girl with RDEB who developed a large SCC on the left knee. At 6 months of evolution it was resected and covered with an autologous skin graft. To our knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 14 publications
0
34
0
1
Order By: Relevance
“…The risk of malignancy starts from the second decade onwards. The youngest age reported so far in the literature of SCC complicating RDEB is 13 years 6 . In our case, SCC was detected at the age of 6 years.…”
Section: Discussionmentioning
confidence: 54%
“…The risk of malignancy starts from the second decade onwards. The youngest age reported so far in the literature of SCC complicating RDEB is 13 years 6 . In our case, SCC was detected at the age of 6 years.…”
Section: Discussionmentioning
confidence: 54%
“…4 These cancers usually appear between the second and third decades of life; however, any non-healing, atypical appearing wound, especially one with exuberant scar tissue, should raise suspicion for SCC. 5 A fragment of collagen VII known as the amino-terminal non-collagenous domain has been established to be required for Ras-driven human epidermal tumorigenesis; it is hypothesized that retention of non-collagenous domain sequences could help explain the increased risk for SCC in RDEB. 6 A 2009 systematic review of randomized controlled trials of treatments for inherited forms of epidermolysis bullosa revealed no reliable evidence for interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As it was mentioned above, there is a well-known relationship with actinic keratosis from which most of the invasive tumors arise 5,31 . In a similar fashion to BCC, cSCC is notoriously more frequently found in the context of certain syndromes and genetic disorders such as xeroderma pigmentosum, 32, 33 epidermolysis bullosa 34 , pansclerotic morphea of childhood 35 [44][45][46] .…”
Section: Epidemiologymentioning
confidence: 99%